The impact of financial management and public policy on economic performance: A time series analysis in Bengkulu - Fitriani Ariska; Pakri Pakri (Privietlab, 2024)
This study examines the relationship between financial management and public policy on economic performance in Bengkulu, Indonesia, using a time series approach over four years. The research incorporates eight key variables, including government spending, tax revenue, inflation rate, interest rate, public debt, economic growth, financial inclusion, and investment level. Employing the EViews software for data analysis, the study applies econometric techniques such as unit root tests, cointegration analysis, and vector error correction models (VECM) to assess short-term and long-term interactions among the variables. The findings highlight the significant role of fiscal policies and financial management in shaping economic stability and growth. Furthermore, the results provide policy implications for improving financial strategies to enhance economic performance in Bengkulu. This study contributes to the existing literature by offering empirical evidence on the interplay between financial management and public policy within a localized economic context.